PEER PRESSURE AS A MODERATOR IN THE RELATIONSHIP BETWEEN PARENTAL INVOLVEMENT AND STUDENT ENGAGEMENT AMONG MALAYSIAN INDIAN SECONDARY SCHOOL STUDENTS - Vijayakumaran, Naranthiran; Yusof, Halimah Mohd; Oulaganathan, Sivakanthan; Manalan, Tharshini S; Leong , Pui Huang; Sam , Yet Huat (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates the moderating role of peer pressure in the relationship between parental involvement and student engagement among Malaysian Indian secondary school students. Grounded in Astin’s Student Involvement Theory (1987), the study examines how various dimensions of parental involvement: supportive, controlling, learning environment management, and participation in homework are interact with peer pressure to shape student behavioural, emotional, and cognitive engagement. Data were collected from 181 Form Two Malaysian Indian students using a structured questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings revealed that peer pressure moderates the relationship between parental involvement and student engagement. Notably, high levels of peer pressure can diminish the effects of parental involvement. The study highlights the critical need to consider peer dynamics alongside family-based strategies to foster student educational engagement. Implications for educators, parents, and policymakers are discussed, with recommendations for culturally sensitive engagement interventions.